Oromucosal Alginate Films with Zein Nanoparticles as a Novel Delivery System for Digoxin - Daniela A. Rodrigues; Sónia P. Miguel; Jorge Loureiro; Maximiano Ribeiro; Fátima Roque; Paula Coutinho (MDPI AG, 2021)
Digoxin is a hydrophobic drug used for the treatment of heart failure that possesses a narrow therapeutic index, which raises safety concerns for toxicity. This is of utmost relevance in specific populations, such as the elderly. This study aimed to demonstrate the potential of the sodium alginate films as buccal drug delivery system containing zein nanoparticles incorporated with digoxin to reduce the number of doses, facilitating the administration with a quick onset of action. The film was prepared using the solvent casting method, whereas nanoparticles by the nanoprecipitation method. The nanoparticles incorporated with digoxin (0.25 mg/mL) exhibited a mean size of 87.20 ± 0.88 nm, a polydispersity index of 0.23 ± 0.00, and a zeta potential of 21.23 ± 0.07 mV. Digoxin was successfully encapsulated into zein nanoparticles with an encapsulation efficiency of 91% (±0.00). Films with/without glycerol and with different concentrations of ethanol were produced. The sodium alginate (SA) films with 10% ethanol demonstrated good performance for swelling (maximum of 1474%) and mechanical properties, with a mean tensile strength of 0.40 ± 0.04 MPa and an elongation at break of 27.85% (±0.58), compatible with drug delivery application into the buccal mucosa. The current study suggests that SA films with digoxin-loaded zein nanoparticles can be an effective alternative to the dosage forms available on the market for digoxin administration.